(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nanomaterials technology and development have successfully served progress various scientific areas. Because of its biocompatibility, special physicochemical characteristics and cost-effective mass production, zinc oxide (ZnO)-based nanocomposites has been the most viable techniques for biological applications. Latest developments in nano-engineering, moreover, technology enables the generation of specific three-dimensional structures and surface properties of ZnO nanocomposites which are efficiently developed on behalf of in vivo tests. Herein, our study showed current developments on the use of various ZnO NCs, by a specific emphasis of use. Production like immunotherapeutic vaccines adjuvants and tumor, and also their interfacial properties that interfere with both the immune system and the in vivo possible toxic impact. Eventually, as therapeutic and preventive vaccines towards pathogens, we summarise promising evidence-of-concept applications towards cancer. Moreover, the analysis of these composites is of highly significance due to their enhanced multifunctional properties, such as their mechanical, filter and antibacterial activities, the food processing materials sector. The knowledge of a nano-based biological frameworks among ZnO-based NCs and their immune-based response, along with the biologically effective strategy of nanomaterials by means of nano-architectural expertise, may open novel opportunities for the expansion of the therapeutic use of ZnO nanocomposites as an innovative platform for vaccines.